2001
DOI: 10.1111/j.1749-6632.2001.tb03646.x
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine‐Induced Dopaminergic Neurotoxicity: Role of Peroxynitrite and Neuroprotective Role of Antioxidants and Peroxynitrite Decomposition Catalysts

Abstract: Oxidative stress, reactive oxygen (ROS), and nitrogen (RNS) species have been known to be involved in a multitude of neurodegenerative disorders such as Parkinson's disease (PD), Alzheimer's disease (AD), and amyotrophic lateral sclerosis (ALS). Both ROS and RNS have very short half‐lives, thereby making their identification very difficult as a specific cause of neurodegeneration. Recently, we have developed a high performance liquid chromatography/electrochemical detection (HPLC/EC) method to identify 3‐nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(101 citation statements)
references
References 57 publications
(100 reference statements)
2
99
0
Order By: Relevance
“…Like other amphetamines, methamphetamine increases extracellular levels of monoamines by disrupting vesicular storage and reversing the plasma membrane transporter [262][263][264]. While methamphetamine's effects upon the monoaminergic systems have received considerable experimental attention [for reviews, [264][265][266][267][268][269][270], less is known regarding the regulation of corticoaccumbens glutamate and glutamate receptor expression by amphetamine and methylated analogs. Acute administration of amphetamines is reported to produce either no change or a delayed rise in extracellular glutamate levels within striatal regions [59][60][61][62]271,272], while an acute injection of methamphetamine, but not amphetamine, elevates PFC glutamate levels [271].…”
Section: Homers and Methamphetaminementioning
confidence: 99%
“…Like other amphetamines, methamphetamine increases extracellular levels of monoamines by disrupting vesicular storage and reversing the plasma membrane transporter [262][263][264]. While methamphetamine's effects upon the monoaminergic systems have received considerable experimental attention [for reviews, [264][265][266][267][268][269][270], less is known regarding the regulation of corticoaccumbens glutamate and glutamate receptor expression by amphetamine and methylated analogs. Acute administration of amphetamines is reported to produce either no change or a delayed rise in extracellular glutamate levels within striatal regions [59][60][61][62]271,272], while an acute injection of methamphetamine, but not amphetamine, elevates PFC glutamate levels [271].…”
Section: Homers and Methamphetaminementioning
confidence: 99%
“…There is evidence that oxidative stress arises from peroxidative generation of dopamine quinone from dopamine released by METH into the cytoplasm from synaptic vesicles via reverse transport through the dopamine transporter (257,258). RNS (peroxynitrite) also appear to play a major role in METH-induced dopaminergic neurotoxicity (259).…”
Section: Role Of Oxidative Stress In the Pathogenesis Of Pd And Modelmentioning
confidence: 99%
“…METH-induced increases in extracellular concentrations of striatal DA and GLU (O'Dell et al, 1991;Stephans and Yamamoto, 1994) are known to contribute to the observed nerve terminal damage (Sonsalla et al, 1989;Nash and Yamamoto, 1992;Imam et al, 2001). Unlike METH-induced striatal DA release, which occurs directly via reverse transport, METH-induced striatal GLU release is indirect and initiated by the activation of the D 1 -associated striatonigral GABAergic pathway (Mark et al, 2004).…”
Section: Introductionmentioning
confidence: 99%